Carbon cloth loaded heterostructure material as well as preparation method and application thereof
By loading bimetallic sulfide salts of tile-shaped nanosheets on the carbon cloth of the negative electrode of the lithium-ion battery, forming a three-dimensional network structure, the problem of poor rate performance, specific capacity and cycle performance of the negative electrode of the lithium-ion battery is solved, and high energy density and excellent cycle life are achieved.
Patent Information
- Application Number
- CN202411906439.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
The rate performance, specific capacity and circulation performance of the negative electrode of lithium-ion batteries are poor, making it difficult to achieve large-scale commercial applications.
Carbon cloth loaded heterostructure materials, including carbon cloth and bimetallic sulfide salts loaded on the surface of the carbon cloth, are grown on the surface of the carbon fiber conductive network in the form of tile-covered nanosheets to form a three-dimensional network structure.
Significantly improve the rate performance, specific capacity and cycle performance of the composite negative electrode, and achieve high energy density, excellent cycle life and fast charging and discharging capabilities.
Smart Images

Figure CN119695148A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a carbon cloth-loaded heterogeneous structure material, a preparation method and application thereof. Background Art
[0002] As we all know, graphite, as the main commercial negative electrode in lithium-ion batteries, has poor layered structure stability. After a long period of charge and discharge cycles, its structure is prone to collapse, resulting in a serious decrease in specific capacity and a significant shortening of energy storage life. The development of new negative electrode materials with high energy density has never stopped.
[0003] Insertion of carbon-based anodes (hard carbon, etc.) can lead to relatively improved electrochemical performance. However, their output capacity is less than 300 mAh g -1 , which limits its practical application in lithium-ion batteries. As a potential electrode material, transition metal sulfides have higher theoretical specific capacity than intercalated carbonaceous materials based on the storage mechanism of multiple electron transfer. Compared with oxides, transition metal sulfides generally have superior electronic conductivity and structural stability.
[0004] However, due to problems such as slow kinetics and volume change during lithiation / delithiation, the cycling performance of transition metal sulfides is still unsatisfactory. To alleviate the above problems, technicians have made great efforts, and combining nanostructured transition metal sulfides with highly conductive scaffolds is considered to be a common and effective strategy, which can not only alleviate the Li + The structural changes caused by embedding / extraction can also improve electronic conductivity, thereby improving the electrochemical performance of the negative electrode of lithium-ion batteries. However, the improvement of the rate performance, specific capacity and cycle performance of the negative electrode is still limited, making it difficult to achieve large-scale commercial application. Summary of the invention
[0005] The main purpose of the present invention is to provide a carbon cloth-loaded heterostructure material, a preparation method and application thereof, so as to solve the problems of poor rate performance, specific capacity and cycle performance of the negative electrode of lithium-ion batteries in the prior art.
[0006] In order to achieve the above object, according to one aspect of the present invention, a carbon cloth-loaded heterostructure material is provided, comprising a carbon cloth and a bimetallic sulfide salt loaded on the surface of the carbon cloth, wherein the carbon cloth has a carbon fiber conductive network, and the bimetallic sulfide salt grows on the surface of the carbon fiber conductive network in the form of shingled nanosheets to form a three-dimensional network structure; wherein the metal in the bimetallic sulfide salt includes zinc. The carbon cloth-loaded heterostructure material of the present invention can significantly improve the rate performance, specific capacity and cycle performance of the composite negative electrode.
[0007] Further, the bimetallic sulfide salt includes one or more of nickel zinc sulfide, iron zinc sulfide, cobalt zinc sulfide and aluminum zinc sulfide. The above bimetallic sulfide salt has a higher theoretical capacity and can provide more active sites, thereby improving the specific capacity.
[0008] Furthermore, by weight percentage, the carbon cloth accounts for 85-88% of the carbon cloth-loaded heterostructure material, and the bimetallic sulfide salt accounts for 12-15% of the carbon cloth-loaded heterostructure material, which can better achieve a balance between conductivity and electrochemical activity.
[0009] Furthermore, the maximum length of a single sheet of the shingled nanosheet is 2 to 6 μm; and / or in the carbon fiber conductive network, the diameter of the carbon fiber is 5 to 7 μm. Based on the synergistic effect of the carbon fiber and the nanosheet of the above size, a more efficient three-dimensional conductive skeleton can be formed, the transmission path can be reduced, and a more stable electrochemical reaction can be maintained even at a high current density, with significantly improved cycle stability.
[0010] According to another aspect of the present invention, a method for preparing the carbon cloth-loaded heterostructure material of the present invention is provided, comprising the following steps: step S1, annealing the carbon cloth to obtain a pretreated carbon cloth; step S2, mixing a zinc salt, a second metal salt, urea, hexamethylenetetramine and water to obtain a metal solution; immersing the pretreated carbon cloth in the metal solution to perform a hydrothermal reaction to obtain a precursor; step S3, immersing the precursor in an aqueous solution of a sulfide to perform a sulfurization reaction to obtain a carbon cloth-loaded heterostructure material. The above-mentioned preparation method is simple and easy to operate. The rich surface area of the nanosheets in the prepared carbon cloth-loaded heterostructure material can provide more active sites for electrochemical reactions, thereby significantly improving the rate performance, specific capacity and cycle performance of the composite negative electrode material.
[0011] Furthermore, in step S1, the annealing temperature is 350-450°C and the time is 1.5-2.5h; preferably, before annealing, step S1 also includes the steps of washing and drying the carbon cloth in sequence: ultrasonically washing the carbon cloth with acetone for 50-70min, then ultrasonically washing it with a mixture of ethanol and water for 50-70min, and then drying it at 70-90°C. Under the above conditions, the microstructure of the carbon cloth can be further optimized, its conductivity and thermal stability can be enhanced, while promoting the repair of surface defects, improving the electronic transmission efficiency and structural integrity of the material, and facilitating the rapid transmission and storage of lithium ions, thereby significantly improving the rate performance and cycle performance.
[0012] Further, in step S2, the zinc salt includes zinc nitrate hexahydrate, and the second metal salt includes nickel chloride hexahydrate, iron chloride, cobalt chloride or aluminum chloride; preferably, the weight ratio of the zinc salt to the second metal salt is 1: (2-3); and / or the weight ratio of urea to hexamethylenetetramine is 1: (0.25-0.5); preferably, the weight ratio of the zinc salt to urea is 1: (6-7); and / or the temperature of the hydrothermal reaction is 110-130° C., and the time is 5-7h; preferably, step S2 also includes the following steps: washing the precursor with a mixture of ethanol and water for 50-70 minutes, and then drying at 70-90° C. to dryness. It can better promote the uniform deposition of bimetallic sulfides to form a dense and stable nanostructure, increase active sites, optimize the storage capacity of lithium ions, and thus improve the specific capacity.
[0013] Further, in step S3, the sulfide includes one or more of sodium sulfide, sodium sulfide nonahydrate and thiourea; preferably, the ratio of the sum of the weight of the zinc salt and the second metal salt to the weight of the sulfide is 1:(0.65-0.75); and / or the temperature of the sulfurization reaction is 150-170°C, and the time is 5-7h; preferably, step S3 also includes the following steps: washing the carbon cloth-loaded heterostructure material with a mixture of ethanol and water for 50-70min, and then drying it at 70-90°C. The above conditions can further promote the complete conversion of bimetallic sulfides in the sulfurization reaction, forming a highly crystalline and structurally stable heterogeneous nanostructure to increase the storage sites of lithium ions and significantly improve the specific capacity.
[0014] According to another aspect of the present invention, a lithium ion battery negative electrode is provided, comprising the carbon cloth-loaded heterostructure material of the present invention. The negative electrode of the present invention achieves comprehensive performance improvement, and has high energy density, excellent cycle life and fast charge and discharge capability.
[0015] According to another aspect of the present invention, a lithium ion battery is provided, comprising the lithium ion battery negative electrode of the present invention, which has significantly improved rate performance, specific capacity and cycle performance.
[0016] By applying the technical solution of the present invention, the bimetallic sulfide salt is uniformly grown on the carbon fiber conductive network in the carbon cloth in the form of shingle-like nanosheets, and the nanosheets are interconnected and intersected to form a three-dimensional network structure. The abundant blank spaces between the nanosheets can promote the penetration of the electrolyte and the lithiation of the electrode. The shingle-like nanosheets also introduce more active sites. The significant gaps between the nanosheets greatly increase the contact area between the material and the electrolyte, improve the conductivity, and provide more active sites for the electrochemical reaction. The bimetallic sulfide salt can also combine the advantages of multiple components and multiple phases to produce sufficient boundaries and small crystal domains, which helps to achieve fast kinetics that avoid solid-state diffusion and promote ion diffusion. The carbon cloth-loaded heterostructure material of the present invention can significantly improve the rate performance, specific capacity and cycle performance of the composite negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 The SEM image of the carbon cloth-supported heterogeneous structure material according to Example 1 of the present invention is shown;
[0019] Figure 2 The XRD diffraction pattern of the carbon cloth-supported heterostructure material according to Example 1 of the present invention is shown;
[0020] Figure 3 The cyclic performance curve of the carbon cloth-loaded heterogeneous structure material according to Example 1 of the present invention is shown;
[0021] Figure 4 The structure diagram of the soft pack battery according to the first embodiment of the present invention is shown;
[0022] Figure 5 The cycle performance curve of the soft pack battery according to Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0024] As described in the background of the present invention, the prior art has the problem of poor rate performance, specific capacity and cycle performance of the negative electrode of lithium-ion batteries. In order to solve the above problems, in a typical embodiment of the present invention, a carbon cloth-loaded heterostructure material is provided, including a carbon cloth and a bimetallic sulfide salt loaded on the surface of the carbon cloth, wherein the carbon cloth has a carbon fiber conductive network, and the bimetallic sulfide salt grows on the surface of the carbon fiber conductive network in the form of shingled nanosheets to form a three-dimensional network structure; wherein the metal in the bimetallic sulfide salt includes zinc.
[0025] The composite material of the present invention comprises carbon cloth having a carbon fiber conductive network as a base material; bimetallic sulfide salt is uniformly grown on the carbon fiber conductive network in the form of shingle-shaped nanosheets, the nanosheets are interconnected and intersected to form a three-dimensional network structure. The sizes of the bimetallic sulfide salt and the carbon fiber conductive network are both micrometer-level.
[0026] Taking the use of nickel zinc sulfide (ZnNi2S4) as an example of bimetallic sulfide salt, the loading mechanism of the present invention is as follows: ZnNi-precursor is formed on the surface of carbon fiber rod, and then ZnNi-precursor gradually aggregates to form a dense nanosheet layer, and after vulcanization, bimetallic sulfide salt nanosheets are grown on the carbon fiber conductive network in a shingle-like manner. The material of the present invention has a carbon cloth conductive network loaded with ZnNi2S4 3D foam nanosheet (flower) array, in which the nanosheets are interconnected and intersected to form a three-dimensional network structure, and the gaps can be clearly observed. The SEM image of the carbon cloth loaded heterogeneous structure material of an embodiment is shown in FIG. Figure 1 .
[0027] Specifically, carbon cloth mainly provides a stable conductive substrate and a three-dimensional framework to promote the conduction of electrons and ensure the high conductivity of the material, thereby significantly improving the rate performance. The abundant empty space between the nanosheets can promote the penetration of the electrolyte and promote the lithiation of the electrode. The shingled nanosheets introduce more active sites, and the significant gaps between the nanosheets greatly increase the contact area with the electrolyte, improve the conductivity, and provide more active sites for electrochemical reactions. Taking ZnNi2S4 as an example, bimetallic sulfide salts generally have a spinel structure, in which Zn and Ni are located in octahedral and tetrahedral positions, respectively, which can combine the advantages of multiple components and multiple phases. The presence of these multiple phases in ZnNi2S4 produces sufficient boundaries and small crystal domains, which helps to circumvent solid-state diffusion and promote the rapid kinetics of ion diffusion.
[0028] Among them, when the metal in the bimetallic sulfide salt includes zinc, it is more conducive to the formation of shingle-like nanosheets with specific properties to improve electrical properties and have a more stable structure. In addition, metallic zinc can be loaded on the surface of the carbon cloth in the form of zinc-metal precursor during the formation process, and subsequently form nanosheets with chemical connection with the carbon cloth. Compared with the conventional physical coating form, the chemical connection form can significantly enhance the connection strength between the bimetallic sulfide salt and the carbon cloth, and is less likely to fall off during use.
[0029] In addition, compared with single metal sulfide salts such as NiS and ZnS, the Ni 2+ and Zn 2+ The presence of makes it have more redox reaction sites and multi-electron reaction mechanism, so it has higher electrochemical activity. In summary, the carbon cloth loaded heterostructure material of the present invention can significantly improve the rate performance, specific capacity and cycle performance of the composite negative electrode.
[0030] In a preferred embodiment, the bimetallic sulfide salt includes one or more of nickel zinc sulfide, iron zinc sulfide, cobalt zinc sulfide and aluminum zinc sulfide. The above-mentioned bimetallic sulfide salt has a higher theoretical capacity and can provide more active sites, thereby improving the specific capacity. At the same time, the unique three-dimensional foam nanoflower structure formed can further increase the contact area between the electrode and the electrolyte, promote the rapid transmission of electrons and ions, and enhance the rate performance. The bimetallic elements can also optimize the electronic structure of the material, improve the electronic conductivity, and reduce the polarization during the electrochemical reaction, thereby improving the cycle stability and improving the performance consistency under long-term use. In addition, the above-mentioned bimetallic sulfide salt is more conducive to synergizing with the carbon cloth conductive network to further alleviate the volume expansion caused by the lithiation / delithiation process, thereby further enhancing the cycle performance.
[0031] In order to better achieve a balance between conductivity and electrochemical activity, in a preferred embodiment, by weight percentage, carbon cloth accounts for 85-88% of the carbon cloth-loaded heterostructure material, and bimetallic sulfide salt accounts for 12-15% of the carbon cloth-loaded heterostructure material. The above-mentioned carbon fiber conductive network as a substrate can further improve the structural stability, better alleviate the stress caused by volume change during the cycle, and enhance the cycle performance. The remaining proportion of bimetallic sulfide salt as an active substance, based on its high theoretical capacity and multi-electron reaction characteristics, is more conducive to improving the specific capacity of the composite negative electrode, increasing active sites, and promoting the rapid insertion and extraction of lithium ions, and ultimately further optimizing the rate performance and cycle stability.
[0032] In a preferred embodiment, the maximum length of a single sheet of the shingled nanosheet is 2 to 6 μm; and / or in the carbon fiber conductive network, the diameter of the carbon fiber is 5 to 7 μm. The above-mentioned tiny size of the nanosheet is more conducive to increasing the surface area, providing more abundant active sites, accelerating the insertion and extraction of lithium ions, and significantly improving the specific capacity. At the same time, the micron-level carbon fiber not only serves as a conductive network, but also can further promote the full penetration of the electrolyte and the effective transmission of ions, thereby optimizing the rate performance. Based on the synergistic effect of carbon fibers and nanosheets of the above size, a more efficient three-dimensional conductive skeleton can be formed, the transmission path can be reduced, and a more stable electrochemical reaction can be maintained even at high current density, with significantly improved cycle stability.
[0033] In another typical embodiment of the present invention, a method for preparing the above-mentioned carbon cloth-loaded heterostructure material of the present invention is also provided, comprising the following steps: step S1, annealing the carbon cloth to obtain a pretreated carbon cloth; step S2, mixing a zinc salt, a second metal salt, urea, hexamethylenetetramine and water to obtain a metal solution; immersing the pretreated carbon cloth in the metal solution to perform a hydrothermal reaction to obtain a precursor; step S3, immersing the precursor in an aqueous solution of a sulfide to perform a sulfurization reaction to obtain a carbon cloth-loaded heterostructure material.
[0034] The formation of bimetallic sulfide salt nanosheets can be explained according to the Kirkendall effect. Specifically, the present invention first anneals the carbon cloth to generate oxygen-containing functional groups on its surface to improve the hydrophilicity of its surface, thereby obtaining a pretreated carbon cloth; then zinc salt, a second metal salt, urea, hexamethylenetetramine and water are mixed to obtain a metal solution, and the pretreated carbon cloth is immersed in the metal solution and subjected to a hydrothermal reaction. Taking ZnNi2S4 nanosheets as an example, the mechanism is that urea is hydrolyzed to produce carbon dioxide, and carbon dioxide drives metal ions to diffuse outward, forming a ZnNi-precursor on the surface of the carbon fiber rod, and the ZnNi-precursor gradually aggregates to form a dense nanosheet layer to obtain a precursor.
[0035] Finally, the precursor is immersed in an aqueous solution of sulfide and subjected to a sulfurization reaction. The high-temperature pyrolysis of the sulfide leads to S 2- The release of ions, S 2- ions react with the ZnNi-precursor to generate the corresponding ZnNi2S4, which inherits the precursor morphology well and wraps around the carbon fiber like a physical barrier. 2+ and Ni 2+ The diffusion rate is relative to S 2-The growth rate of the nanosheets is different, so the ZnNi-precursor gradually transforms into a foamy ZnNi2S4 nanosheet, which results in a very representative morphology of the ZnNi2S4 nanosheet, and a carbon cloth-loaded heterostructure material is obtained. The above preparation method is simple and easy to operate. The rich surface area of the nanosheets in the prepared carbon cloth-loaded heterostructure material can provide more active sites for the electrochemical reaction, thereby significantly improving the rate performance, specific capacity and cycle performance of the composite negative electrode material.
[0036] In a preferred embodiment, in step S1, the annealing temperature is 350-450°C and the time is 1.5-2.5h; before annealing, step S1 also includes the steps of sequentially cleaning and drying the carbon cloth: ultrasonically cleaning the carbon cloth with acetone for 50-70min, then ultrasonically cleaning it with a mixture of ethanol and water for 50-70min, and then drying it at 70-90°C until dry. The sequential cleaning with acetone and ethanol can effectively remove organic impurities and residues on the surface of the carbon cloth, improve the purity and surface activity of the material, provide a clean substrate for the uniform growth of subsequent nanosheets, and promote good contact and bonding between the active material and the conductive network. The annealing treatment under the above conditions can further optimize the microstructure of the carbon cloth, enhance its conductivity and thermal stability, promote the repair of surface defects, improve the electronic transmission efficiency and structural integrity of the material, and facilitate the rapid transmission and storage of lithium ions, thereby significantly improving the rate performance and cycle performance.
[0037] In order to better promote the uniform deposition of bimetallic sulfides to form a dense and stable nanostructure, increase active sites, optimize the storage capacity of lithium ions, and thus improve the specific capacity, in a preferred embodiment, in step S2, the zinc salt includes zinc nitrate hexahydrate, and the second metal salt includes nickel chloride hexahydrate, iron chloride, cobalt chloride or aluminum chloride; preferably, the weight ratio of the zinc salt to the second metal salt is 1: (2 to 3); and / or the weight ratio of urea to hexamethylenetetramine is 1: (0.25 to 0.5); preferably, the weight ratio of the zinc salt to urea is 1: (6 to 7); and / or the temperature of the hydrothermal reaction is 110 to 130° C., and the time is 5 to 7 hours; preferably, step S2 also includes the following steps: washing the precursor with a mixture of ethanol and water for 50 to 70 minutes, and then drying it at 70 to 90° C. to dryness. When the ratio of urea to hexamethylenetetramine and the ratio of urea to zinc salt are within the above range, it is more conducive to improving the growth rate and morphology of the precursor and nanosheets, building a more efficient lithium ion transmission channel, and thus enhancing the rate performance. The above hydrothermal reaction conditions are more conducive to the high-quality formation of nanostructures, improving the electronic conductivity and structural consistency of the material, thereby improving the cycle performance. The washing and drying steps can effectively remove by-products, reduce the negative impact of impurities on electrochemical performance, and further improve the purity and reactivity of the material.
[0038] In a preferred embodiment, in step S3, the sulfide includes one or more of sodium sulfide, sodium sulfide nonahydrate and thiourea; preferably, the sum of the weights of the zinc salt and the second metal salt is in a ratio of 1:(0.65-0.75) to the weight of the sulfide; and / or the temperature of the sulfurization reaction is 150-170°C, and the time is 5-7h; preferably, step S3 also includes the following steps: the carbon cloth-loaded heterostructure material is washed with a mixture of ethanol and water for 50-70min, and then dried at 70-90°C. Within the above material ratio range, the complete conversion of bimetallic sulfides in the sulfurization reaction can be further promoted to form a highly crystalline and structurally stable heterogeneous nanostructure to increase the storage sites of lithium ions and significantly improve the specific capacity. The above sulfurization reaction parameters can further improve the depth and uniformity of the sulfurization process, optimize the morphology and size of the nanostructure, construct a fast ion transport channel, and enhance the rate performance. In addition, washing and drying with ethanol and water can effectively remove residual reaction by-products, improve the surface cleanliness and reaction activity of the material, and reduce the polarization of the electrochemical reaction, thereby further improving the cycle performance.
[0039] In another typical embodiment of the present invention, a lithium-ion battery negative electrode is also provided, comprising the carbon cloth-loaded heterostructure material of the present invention. In the above-mentioned negative electrode, the three-dimensional stable structure of the carbon cloth conductive network provides an efficient electron conduction path, which can significantly enhance the conductivity of the electrode, increase the rate of electrochemical reaction, and improve the rate performance of the battery. Secondly, the loaded bimetallic sulfide nanosheets increase the electrochemical active sites, greatly increase the storage capacity of lithium ions, and thus improve the specific capacity of the battery. Moreover, the three-dimensional network structure of the intersecting nanosheets promotes the penetration of the electrolyte and the uniform diffusion of lithium ions, reduces the structural stress during the cycle, and can greatly enhance the cycle stability of the material. Combining these advantages, the negative electrode of the present invention achieves a comprehensive improvement in performance, with high energy density, excellent cycle life and fast charge and discharge capabilities.
[0040] In another typical embodiment of the present invention, a lithium ion battery is provided, comprising the lithium ion battery negative electrode of the present invention, which has significantly improved rate performance, specific capacity and cycle performance.
[0041] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0042] Example 1
[0043] A carbon cloth-loaded ZnNi2S4 material (CFC@ZnNi2S4), in which, by weight percentage, the carbon cloth accounts for 87% of the carbon cloth-loaded heterogeneous structure material, and the bimetallic sulfide salt accounts for 13%. The preparation method comprises the following steps:
[0044] Step S1: First, ultrasonically clean the carbon cloth with organic solvent acetone for 60 minutes, and then ultrasonically clean the carbon cloth with ethanol and deionized water for 60 minutes. Put the carbon cloth into a drying oven at 80°C for drying. Finally, take out the dried carbon cloth and put it into a muffle furnace for annealing at 400°C for 2 hours to obtain a pretreated carbon cloth.
[0045] Step S2: 0.297g Zn(NO3)2·6H2O, 0.713g NiCl2·6H2O, 2g urea and 0.75g hexamethylenetetramine are dissolved in a reactor containing 75ml of deionized water. The pretreated carbon cloth is immersed in the above reactor, and the reactor is started to heat, the temperature is set to 120°C, and this temperature is maintained for 6 hours. After cooling, the carbon cloth is taken out from the reactor and washed with ethanol and deionized water to remove the residual chemical reagents on the surface of the carbon cloth. Finally, it is placed in a vacuum drying oven at 80°C until it is completely dried to obtain a precursor.
[0046] Step S3: Dissolve 0.72g of sodium sulfide in a reactor containing 75mL of deionized water, and put the precursor in again. Start the reactor to heat, set the temperature to 160°C, and maintain this temperature for 6 hours. After cooling, take out the carbon cloth sample that has been treated with hydrothermal reaction, and wash it with ethanol and deionized water to remove the residual chemical reagents on the surface of the carbon cloth. Finally, put it in a vacuum drying oven at 80°C until it is completely dried to obtain a carbon cloth-loaded heterostructure material.
[0047] Example 2
[0048] The difference from Example 1 is that a carbon cloth loaded with ZnFe2S4 material (CFC@ZnFe2S4); Step S2: 0.297g Zn(NO3)2·6H2O, 0.784g FeCl2·6H2Og, 2g urea and 0.75g hexamethylenetetramine are dissolved in a reactor containing 75ml of deionized water. The pretreated carbon cloth is immersed in the above reactor, the reactor is started for heating, the temperature is set to 120°C, and this temperature is maintained for 6 hours. After cooling, the carbon cloth is taken out from the reactor and washed with ethanol and deionized water to remove residual chemical reagents on the surface of the carbon cloth. Finally, it is placed in a vacuum drying oven at 80°C until it is completely dried to obtain a precursor.
[0049] Example 3
[0050] The difference from Example 1 is that a carbon cloth loaded with ZnCo2S4 material (CFC@ZnCo2S4); Step S2: 0.297g Zn(NO3)2·6H2O, 0.689g CoCl2·6H2Og, 2g urea and 0.75g hexamethylenetetramine are dissolved in a reactor containing 75ml of deionized water. The pretreated carbon cloth is immersed in the above reactor, the reactor is started for heating, the temperature is set to 120°C, and this temperature is maintained for 6 hours. After cooling, the carbon cloth is taken out from the reactor and washed with ethanol and deionized water to remove residual chemical reagents on the surface of the carbon cloth. Finally, it is placed in a vacuum drying oven at 80°C until it is completely dried to obtain a precursor.
[0051] Example 4
[0052] The difference from Example 1 is that a carbon cloth loaded with ZnAl2S4 material (CFC@ZnAl2S4); Step S2: 0.297g Zn(NO3)2·6H2O, 0.438g AlCl3·6H2Og, 2g urea and 0.75g hexamethylenetetramine are dissolved in a reactor containing 75ml of deionized water. The pretreated carbon cloth is immersed in the above reactor, the reactor is started for heating, the temperature is set to 120°C, and this temperature is maintained for 6 hours. After cooling, the carbon cloth is taken out from the reactor, and washed with ethanol and deionized water to remove residual chemical reagents on the surface of the carbon cloth. Finally, it is placed in a vacuum drying oven at 80°C until it is completely dried to obtain a precursor.
[0053] Example 5
[0054] The difference from Example 1 is that, in step S1: first, ultrasonically clean the carbon cloth with organic solvent acetone for 50 minutes, and then ultrasonically clean the carbon cloth with ethanol and deionized water for 50 minutes. The carbon cloth is placed in a drying oven at 70°C for drying. Finally, the dried carbon cloth is taken out and placed in a muffle furnace for annealing at 350°C for 2.5 hours to obtain a pretreated carbon cloth.
[0055] Example 6
[0056] The difference from Example 1 is that, in step S1: first, ultrasonically clean the carbon cloth with organic solvent acetone for 70 minutes, and then ultrasonically clean the carbon cloth with ethanol and deionized water for 70 minutes. The carbon cloth is placed in a drying oven at 90°C for drying. Finally, the dried carbon cloth is taken out and placed in a muffle furnace for annealing at 450°C for 1.5 hours to obtain a pretreated carbon cloth.
[0057] Example 7
[0058] The difference from Example 1 is that, in step S2: 0.297g Zn(NO3)2·6H2O, 0.594g NiCl2·6H2O, 1.78g urea and 0.89g hexamethylenetetramine are dissolved in a reactor containing 75ml of deionized water. The pretreated carbon cloth is immersed in the above reactor, the reactor is started to heat, the temperature is set to 110°C, and this temperature is maintained for 7 hours. After cooling, the carbon cloth is taken out from the reactor, and washed with ethanol and deionized water to remove the residual chemical reagents on the surface of the carbon cloth. Finally, it is placed in a vacuum drying oven at 70°C until it is completely dried to obtain a precursor.
[0059] Example 8
[0060] The difference from Example 1 is that, in step S2: 0.297g Zn(NO3)2·6H2O, 0.861g NiCl2·6H2O, 2.08g urea and 0.52g hexamethylenetetramine are dissolved in a reactor containing 75ml of deionized water. The pretreated carbon cloth is immersed in the above reactor, the reactor is started to heat, the temperature is set to 130°C, and this temperature is maintained for 5 hours. After cooling, the carbon cloth is taken out from the reactor, and washed with ethanol and deionized water to remove the residual chemical reagents on the surface of the carbon cloth. Finally, it is placed in a vacuum drying oven at 90°C until it is completely dried to obtain a precursor.
[0061] Example 9
[0062] The difference from Example 1 is that, in step S3: 0.66 g of sodium sulfide is dissolved in a reactor containing 75 mL of deionized water, and the precursor is put in again. The reactor is started to heat, the temperature is set to 150°C, and this temperature is maintained for 7 hours. After cooling, the carbon cloth sample treated with hydrothermal reaction is taken out, and it is washed with ethanol and deionized water to remove the residual chemical reagents on the surface of the carbon cloth. Finally, it is placed in a vacuum drying oven at 70°C until it is completely dried to obtain a carbon cloth-loaded heterostructure material.
[0063] Example 10
[0064] The difference from Example 1 is that, in step S3: 0.76 g of sodium sulfide is dissolved in a reactor containing 75 mL of deionized water, and the precursor is put in again. The reactor is started to heat, the temperature is set to 170°C, and this temperature is maintained for 5 hours. After cooling, the carbon cloth sample treated with hydrothermal reaction is taken out, and it is washed with ethanol and deionized water to remove the residual chemical reagents on the surface of the carbon cloth. Finally, it is placed in a vacuum drying oven at 90°C until it is completely dried to obtain a carbon cloth-loaded heterostructure material.
[0065] Embodiment 11
[0066] The difference from Example 1 is that, by weight percentage, the carbon cloth accounts for 85% of the carbon cloth-loaded heterogeneous structure material, and the bimetallic sulfide salt accounts for 15%.
[0067] Example 12
[0068] The difference from Example 1 is that, by weight percentage, the carbon cloth accounts for 88% of the carbon cloth-loaded heterogeneous structure material, and the bimetallic sulfide salt accounts for 12%.
[0069] Comparative Example 1
[0070] The difference from Example 1 is that NiS is loaded on the surface of the carbon cloth.
[0071] Comparative Example 2
[0072] The difference from Example 1 is that ZnS is loaded on the surface of the carbon cloth.
[0073] Comparative Example 3
[0074] The difference from Example 1 is that, in step S2: 0.297g Zn(NO3)2·6H2O, 0.713g NiCl2·6H2O, 0.72g sodium sulfide, 2g urea and 0.75g hexamethylenetetramine are dissolved in a reactor containing 150ml of deionized water. The pretreated carbon cloth is immersed in the above reactor, the reactor is started for heating, the temperature is set to 160°C, and this temperature is maintained for 6 hours. After cooling, the carbon cloth sample treated with hydrothermal reaction is taken out, and it is washed with ethanol and deionized water to remove the residual chemical reagents on the surface of the carbon cloth. Finally, it is placed in a vacuum drying oven at 80°C until it is completely dried to obtain a carbon cloth-loaded heterostructure material.
[0075] Performance Test:
[0076] The materials prepared in the above embodiments and comparative examples were applied to the negative electrode of a flexible lithium-ion battery and performance tests were performed. The results are shown in Table 1.
[0077]
Coin cell battery
[0078] Lithium-ion battery assembly: CR2032 coin-shaped cells were used to perform electrochemical tests on carbon cloth-loaded heterostructure materials. The prepared material was directly used as the working electrode, and lithium foil (lithium sheet) was used as the counter electrode. The two electrodes were cut into discs with a diameter of 1.2 cm, and the loading amount of ZnNi2S4 on the carbon cloth conductive network was 0.1 g; Celgard 2400 was used as a separator, and 1M LiPF6 was added to ethylene carbonate (EC) / diethyl carbonate (DEC) / dimethyl carbonate (DMC) (volume ratio of 1:1:1) as the electrolyte; the battery was assembled in an argon-filled glove box, and the H2O and O2 contents were kept below 0.1 ppm.
[0079] The SEM image of the carbon cloth-loaded heterostructure material of Example 1 is shown in Figure 1 , XRD diffraction pattern see Figure 2 .from Figure 1 It can be seen that the carbon fiber rods are covered with ZnNi2S4 nanosheets in a shingle-like manner. The nanosheets are interconnected and cross-linked to form a three-dimensional network structure. Figure 2 It can be seen that the diffraction peaks of the sample are consistent with the corresponding JCPDS card, and ZnNi2S4 is 36-0788. The sample ZnNi2S4 has 5 obvious diffraction peaks of 27.3°, 35.7°, 54°, 56.4°, and 63.8°, corresponding to 5 crystal planes (110), (101), (211), (220), and (310), respectively. The diffraction peaks of ZnNi2S4 are characterized by dwarfing and broadening, indicating that the synthesized ZnNi2S4 is poorly crystalline and has a nanoscale size. The sample CFC@ZnNi2S4 has two broad peaks at 25.4° and 43.2°, which is because the sample contains carbon cloth (CFC), which is consistent with the XRD spectrum of pure CFC. XRD did not detect the diffraction peaks of other materials except the carbon cloth substrate, indicating that the synthesized ZnNi2S4 has a high purity.
[0080] However, the materials prepared in Comparative Examples 1 to 3 are relatively loose, irregular in shape, unevenly distributed, easily fall off during the cycle, and have poor cycle performance.
[0081] The specific capacity test results of the carbon cloth-loaded heterogeneous structure material of Example 1 are shown in Table 1, and the cycle performance curve is shown in Figure 3 As shown in the figure, it can be found that the electrode CFC@ZnNi2S4 at 0.1A·g -1 After 100 cycles at a current density of 2026.2 mAh g -1 High discharge specific capacity, capacity retention rate is 98.24%, with good specific capacity and capacity retention rate. Compared with single metal sulfide salts NiS and ZnS, the double metal sulfide salt loaded by the present invention is more conducive to improving the cycle performance.
[0082]
Soft pack battery
[0083] The soft pack battery was assembled according to the materials and steps of the CR2032 coin cell, and the electrochemical test of the whole battery was carried out.
[0084] The structure diagram of the CFC@ZnNi2S4||Li foil soft pack battery of Example 1 is shown in FIG. Figure 4 As shown, CFC@ZnNi2S4 is used as the negative electrode and lithium foil / lithium sheet (Li foil) is used as the positive electrode.
[0085] The soft pack battery of Example 1 has a current density of 0.5A·g -1The capacity retention rate after 100 cycles is shown in Table 1, and the cycle performance curve is shown in Figure 5 As shown in the cycle data, the soft pack battery still has 322.60 mAh g after 100 cycles. -1 The discharge specific capacity and capacity retention rate are 94.13%, indicating that it has excellent cycle life and capacity retention rate, which can meet the needs of long-term use. In addition, the coulombic efficiency of the soft-pack battery is close to 100%, indicating its good reversibility.
[0086] Table 1
[0087]
[0088] As can be seen from the above, compared with the comparative example, the bimetallic sulfide salts in the embodiments of the present invention are uniformly grown on the carbon fiber conductive network in the carbon cloth in the form of shingled nanosheets, and the nanosheets are interconnected and intersected to form a three-dimensional network structure. The abundant blank spaces between the nanosheets can promote the penetration of the electrolyte and promote the lithiation of the electrode. The shingled nanosheets also introduce more active sites. The significant gaps between the nanosheets greatly increase the contact area between the material and the electrolyte, improve the conductivity, and can provide more active sites for the electrochemical reaction. The bimetallic sulfide salts can also combine the advantages of multiple components and multiple phases to produce sufficient boundaries and small crystal domains, which helps to achieve rapid kinetics that avoid solid-state diffusion and promote ion diffusion. The carbon cloth-loaded heterostructure material of the present invention can significantly improve the rate performance, specific capacity and cycle performance of the composite negative electrode.
[0089] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the overall effect is better.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A carbon cloth-loaded heterogeneous structure material, characterized in that: It comprises a carbon cloth and a bimetallic sulfide salt loaded on the surface of the carbon cloth, wherein: The carbon cloth has a carbon fiber conductive network, and the bimetallic sulfide salt grows on the surface of the carbon fiber conductive network in the form of shingle-like nanosheets to form a three-dimensional network structure; Wherein, the metal in the double metal sulfide salt includes zinc.
2. The carbon cloth-loaded heterostructure material according to claim 1, characterized in that: The bimetallic sulfide salt includes one or more of nickel zinc sulfide, iron zinc sulfide, cobalt zinc sulfide and aluminum zinc sulfide.
3. The carbon cloth-loaded heterostructure material according to claim 1 or 2, characterized in that: In terms of weight percentage, the carbon cloth accounts for 85-88% of the carbon cloth-loaded heterostructure material, and the bimetallic sulfide salt accounts for 12-15% of the carbon cloth-loaded heterostructure material.
4. The carbon cloth-loaded heterostructure material according to any one of claims 1 to 3, characterized in that: The maximum length of a single sheet of the shingled nanosheet is 2 to 6 μm; and / or In the carbon fiber conductive network, the diameter of the carbon fiber is 5 to 7 μm.
5. The method for preparing a carbon cloth-loaded heterostructure material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S1, annealing the carbon cloth to obtain a pretreated carbon cloth; Step S2, mixing zinc salt, a second metal salt, urea, hexamethylenetetramine and water to obtain a metal solution; Immersing the pretreated carbon cloth in the metal solution to perform a hydrothermal reaction to obtain a precursor; Step S3, immersing the precursor in an aqueous solution of sulfide to perform a sulfurization reaction to obtain the carbon cloth-loaded heterostructure material.
6. The preparation method according to claim 5, characterized in that: In the step S1, The annealing temperature is 350-450°C and the time is 1.5-2.5h; Preferably, before the annealing, the step S1 further comprises the steps of sequentially cleaning and drying the carbon cloth: ultrasonically cleaning the carbon cloth with acetone for 50 to 70 minutes, then ultrasonically cleaning the carbon cloth with a mixture of ethanol and water for 50 to 70 minutes, and then drying at 70 to 90° C. until dry.
7. The preparation method according to claim 5 or 6, characterized in that: In the step S2, The zinc salt comprises zinc nitrate hexahydrate, and the second metal salt comprises nickel chloride hexahydrate, iron chloride, cobalt chloride or aluminum chloride; preferably, the weight ratio of the zinc salt to the second metal salt is 1:(2-3); and / or The weight ratio of urea to hexamethylenetetramine is 1:(0.25-0.5); preferably, the weight ratio of the zinc salt to urea is 1:(6-7); and / or The temperature of the hydrothermal reaction is 110-130°C and the time is 5-7h; Preferably, the step S2 further comprises the following steps: washing the precursor with a mixture of ethanol and water for 50 to 70 minutes, and then drying at 70 to 90° C. until dry.
8. The preparation method according to any one of claims 5 to 7, characterized in that: In the step S3, The sulfide comprises one or more of sodium sulfide, sodium sulfide nonahydrate and thiourea; preferably, the ratio of the sum of the weight of the zinc salt and the second metal salt to the weight of the sulfide is 1:(0.65-0.75); and / or The temperature of the vulcanization reaction is 150-170°C and the time is 5-7h; Preferably, the step S3 further comprises the following steps: washing the carbon cloth-loaded heterostructure material with a mixture of ethanol and water for 50 to 70 minutes, and then drying at 70 to 90° C. until dry.
9. A negative electrode for a lithium ion battery, characterized in that: The carbon cloth-loaded heterostructure material comprises the carbon cloth-loaded heterostructure material according to any one of claims 1 to 4.
10. A lithium ion battery, characterized in that: The lithium-ion battery negative electrode comprises the negative electrode of claim 9.
Citation Information
Cited By
Carbon cloth-supported heterostructured material, and preparation method therefor and use thereof
WO2026137728A1